A Comparative Epidemiological-Pathology Study Regarding the incidence of Gall Ball Stone - Nagah Bobtina; Amina Baleid; Ali I. Abduella Sati; Salma I. Alsunousi; Iman Idris Amghaiab (African Journal of Advanced Pure and Applied Sciences, 2025)
This retrospective epidemiological study, conducted at Al Jala Hospital in Benghazi, Libya, from 2020 to 2023, investigated the incidence of gallstone disease in relation to age and gender. The study also included a comparative pathological analysis of normal gallbladder tissue from healthy individuals and abnormal tissue from patients with gallbladder cancer. A total of 886 patients with gallstones, aged 18 to 65 years, were included in the study. The majority were female (83%), with males making up the remaining 17%. Results demonstrated a strong association between gallstone formation and age, with the highest incidence observed in the 36–45 age group. Notably, a significant increase in cases was also found among younger individuals (18–36 years) in the final year of the study. The gender-specific nature of the disease was evident, with females showing a much higher prevalence of 86% compared to males. In conclusion, the study affirms that females are more susceptible to gallstone formation than males, and that the incidence of this condition has been rising among younger age groups in recent years. These findings underscore the need for targeted health strategies to address the growing prevalence of gallstone disease, particularly among high-risk populations.